2020
DOI: 10.1242/dev.182907
|View full text |Cite
|
Sign up to set email alerts
|

A design principle for floral organ number and arrangement in flowers with bilateral symmetry

Abstract: The bilateral symmetry of flowers is a striking morphological achievement during floral evolution, providing high adaptation potential for pollinators. The symmetry can appear when floral organ primordia developmentally initiate. Primordia initiation at the ventral and dorsal sides of the floral bud is differentially regulated by several factors, including external organs of the flower and CYCLOIDEA (CYC) gene homologues, which are expressed asymmetrically on the dorso-ventral axis. It remains unclear how thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 65 publications
(83 reference statements)
0
15
1
Order By: Relevance
“…The expression patterns of genes can be different between the terminal and lateral flowers, depending on distinct genetic regulation between the terminal and lateral flowers (Rudall and Bateman 2003 ), or whether they have an inflorescence meristem to provide positional information. Such positional information, either physical or chemical, can cause differences in floral organ positioning (Nakagawa et al 2020 ). A variation in floral phyllotaxis can be generated not only in the initiation of primordia but also after the initiation.…”
Section: Floral Phyllotaxis and Developmentmentioning
confidence: 99%
“…The expression patterns of genes can be different between the terminal and lateral flowers, depending on distinct genetic regulation between the terminal and lateral flowers (Rudall and Bateman 2003 ), or whether they have an inflorescence meristem to provide positional information. Such positional information, either physical or chemical, can cause differences in floral organ positioning (Nakagawa et al 2020 ). A variation in floral phyllotaxis can be generated not only in the initiation of primordia but also after the initiation.…”
Section: Floral Phyllotaxis and Developmentmentioning
confidence: 99%
“…Robayo et al (2020) pointed out that the calyx of Loranthaceae degenerated in the evolutionary history of the family. In addition, Nakagawa et al (2020) demonstrated that the dorsal-to-ventral inhibitions and the floral stem cell region (meristem) determine the number and position of the sepals. Based on our previous hybridization analysis, we hypothesize that hybridization events may cause sepals to decrease in number throughout the process of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method of identifying approximate symmetries can be applied to biological objects which can exhibit a variety of symmetry properties, for instance, objects which possess a left/right or anterior/posterior symmetry. This type of symmetry is called bilateral symmetry, where an object produces two mirror image halves when divided along an axis [ 42 ]. For this reason, bilateral symmetry is also called reflection or mirror symmetry.…”
Section: Bilateral Symmetrymentioning
confidence: 99%